Second Toe Systolic Pressure Measurements are Valid Substitutes for First Toe Systolic Pressure Measurements in Diabetic Patients: A Prospective Study. Issue 1 (January 2015) - Bhamidipaty, V.; Dean, A.; Yap, S.L.; Firth, J.; Barron, M.; Allard, B.; Chan, S.T.F.
<x xml:space="preserve">Abstract</x> Objective Toe systolic pressure is a component of the standard vascular and diabetic foot assessment. Until now, clinicians have measured only first toe pressure given a lack of evidence for measurements of the other toes. In diabetic patients, first toe measurements are often not possible because of ulceration or amputation. It was hypothesized that the adjacent second toe systolic pressure measurements would be interchangeable with those of the first toe. Methods A prospective study was performed on 100 participants with diabetes mellitus. Duplicate systolic toe pressures were measured in the first toe and adjacent second toe using the Systoe Automated Toe Pressure System, Systoe Photophlethysmograph Sensor Cuff, and occlusion cuffs measuring 120 × 25 mm for the first toe and 90 × 15 mm for the second toe. Correlation analysis was followed by Ordinary Least Products regression to detect and distinguish fixed and proportional bias between the two toe measurements. The acceptable limits of interchangeable results were defined as 5–10 mmHg. Results Correlation coefficient r = 0.908; p < 0.001. Eighty-two percent of the variations in the second toe measurements were accounted for by knowing the first toe measurements and vice versa. Ordinary Least Products regression showed no fixed or proportional bias between the two methods of measurement: second toe systolic pressure = (−0.579) + (1.038) * first toe systolic pressure. Repeatability analysis showed a 0.5% variation between duplicate measurements. Conclusions This is the first study which demonstrates that second toe systolic pressures are interchangeable with those of the first toe. Second toe pressures can be used in diabetic patients whose first toe pressures cannot be assessed.